Strategy for Increasing Competitiveness of Traditional Markets in the Perspective of Community Satisfaction Based on Traditional Market Management Services : (Case Study on Traditional Markets in the City of Bandung) - Hamijaya, Muhamad Wahyu; Acuviarta (Westscience Press, 2024)
Traditional markets have been the backbone of the economy since ancient times, but currently, the existence of traditional markets is starting to fade along with the development of modern markets and the presence of e-commerce. This research aims to formulate strategies that should be implemented to enhance the competitiveness of traditional markets, particularly 39 traditional markets in the City of Bandung. The parameters used by the researchers are from the perspective of customer satisfaction and service satisfaction regarding the management services of traditional markets. Based on the research results, several important points such as infrastructure improvement, fostering the traditional market ecosystem, and enhancing the class of traditional markets can be pursued to rekindle public interest in shopping at traditional markets in the City of Bandung.